A structure/function investigation into baboon cytochrome P450 side-chain cleavage (CYP11A1) - Storbeck, Karl-Heinz (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Biochemistry))--University of Stellenbosch, 2005.